Increasing freshwater supply to sustainably address global water security at scale - Afeefa Rahman; Praveen Kumar; Francina Dominguez (Scientific Reports, 2022)
Abstract While significant parts of the globe are already facing significant freshwater scarcity, the need for more freshwater is projected to increase in order to sustain the increasing global population and economic growth, and adapt to climate change. Current approaches for addressing this challenge, which has the potential to result in catastrophic outcomes for consumptive needs and economic growth, rely on increasing the efficient use of existing resources. However, the availability of freshwater resources is rapidly declining due to over-exploitation and climate change and, therefore, is unlikely to sustainably address future needs, which requires a rethink of our solutions and associated investments. Here we present a bold departure from existing approaches by establishing the viability of significantly increasing freshwater through the capture of humid air over oceans. We show that the atmosphere above the oceans proximal to the land can yield substantial freshwater, sufficient to support large population centers across the globe, using appropriately engineered structures. Due to the practically limitless supply of water vapor from the oceans, this approach is sustainable under climate change and can transform our ability to address present and future water security concerns. This approach is envisioned to be transformative in establishing a mechanism for sustainably providing freshwater security to the present and future generations that is economically viable.